Long‐term structural and biomass dynamics of virgin Tsuga canadensis–Pinus strobus forests after hurricane disturbance. Issue 3 (3rd February 2017) - D'Amato, Anthony W.; Orwig, David A.; Foster, David R.; Barker Plotkin, Audrey; Schoonmaker, Peter K.; Wagner, Maggie R.
Abstract: The development of old‐growth forests in northeastern North America has largely been within the context of gap‐scale disturbances given the rarity of stand‐replacing disturbances. Using the 10‐ha old‐growth Harvard Tract and its associated 90‐year history of measurements, including detailed surveys in 1989 and 2009, we document the long‐term structural and biomass development of an old‐growth Tsuga canadensis–Pinus strobus forest in southern New Hampshire, USA following a stand‐replacing hurricane in 1938. Measurements of aboveground biomass pools were integrated with data from second‐ and old‐growth T. canadensis forests to evaluate long‐term patterns in biomass development following this disturbance. Ecosystem structure across the Tract prior to the hurricane exhibited a high degree of spatial heterogeneity with the greatest levels of live tree basal area (70–129 m 2 /ha) on upper west‐facing slopes where P. strobus was dominant and intermixed with T. canadensis . Live‐tree biomass estimates for these stratified mixtures ranged from 159 to 503 Mg/ha at the localized, plot scale (100 m 2 ) and averaged 367 Mg/ha across these portions of the landscape approaching the upper bounds for eastern forests. Live‐tree biomass 71 years after the hurricane is more uniform and lower in magnitude, with T. canadensis currently the dominant overstory tree species throughout much of the landscape. Despite only one living P. strobus stem in the 2009 plots (and fewer than five stems known across the entire 10‐ha area), the detrital legacy of this species is pronounced with localized accumulations of coarse woody debris exceeding 237.7–404.2 m 3 /ha where this species once dominated the canopy. These patterns underscore the great sizes P. strobus attained in pre‐European landscapes and its great decay resistance relative to its forest associates. Total aboveground biomass pools in this 71‐year‐old forest (255 Mg/ha) are comparable to those in modern old‐growth ecosystems in the region that also lack abundant white pine. Results highlight the importance of disturbance legacies in affecting forest structural conditions over extended periods following stand‐replacing events and underscore that post‐disturbance salvage logging can alter ecosystem development for decades. Moreover, the dominant role of old‐growth P. strobus in live and detrital biomass pools before and after the hurricane, respectively, demonstrate the disproportionate influence this species likely had on carbon storage at localized scales prior to the widespread, selective harvesting of large P. strobus across the region in the 18th and 19th centuries.